IMPLEMENTASI MESIN PEMERAS MINUMAN EMPON EMPON INSTAN FOOD GRADE GUNA MENJAGA HIGIENITAS DAN KUALITAS USAHA MIKRO KECIL MENENGAH MELATI LOSARI - I Made Wirawan; Sujito Sujito; Arif Nur Afandi; Mokh. Sholihul Hadi; Muhammad Afnan Habibi (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
The product produced by MSMEs Melati Losari is an instant empon empon drink that has many benefits. Problems that can be identified in the field of production are limitations in the process of squeezing the empon empon drink. MSMEs Melati Losari so far still uses manual equipment and methods, namely by placing it between the cloth and then threading it using human power. Thus it takes quite a long time in the process of producing the empon empon drink. The long process reduces productivity in processing this product. From the conditions above, the method and results of this community service are providing appropriate technology by applying an empon- empon drink squeezer machine, which aims to reduce interference during the squeeze process. This empon-empon squeezer is designed to make it easier for users and has a size that is small so that it can be stored easily and has press technology to make it easier during the process of squeezing instant empon-empon drinks. This empon- empon squeezer already uses stainless material to so that the instant empon empon drink during the squeezing process maintains the authentic taste and color of the processed empon empon ingredients. And can meet the recommended food safety standards (food grade) as well as carry out training on the use of tools and maintenance, so that these tools can increase the efficiency, and hygiene of empon empon beverage products, products with high hygiene can improve the quality and quantity of instant empon empon drink production MSMEs Melati Losari.